CREATIVITY AND INNOVATION CROSS-CUTTING AXES IN BUSINESS MANAGEMENT. CASE OF MIPYMES. - Esparza Paz, Franqui Fernando; Esparza Zapata, Erika Margarita; Esparza Zapata, Silvia Fernanda; Vaca Rodriguez, Milton Gustavo (mktDESCUBRE; Vol 1 No 2 (2020): Special Edition 3rd International Scientific Congress of Administrative and Financial Sciences FADE 2019, 2020)
“Creativity and innovation today for companies is a fundamental pillar in competitive development, because its effects are of the utmost importance that generate sources of employment, growth and well-being for society” (González, Riofrío, Sánchez-Quezada, 2017, p. 537). Business dynamics oblige entrepreneurs to make use of elements that allow efficient administration. To evaluate how creativity and innovation constitute transversal axes to improve management in MSMEs in the city of Riobamba is the objective of the research. The study has a mixed approach, with descriptive, cross-sectional and non-experimental research, through the use of a structured survey as a field inquiry instrument, applied to 180 entrepreneurs, managers and administrators of Mipymes, it was carried out the first half of the year 2019 and complemented with documentary and bibliographic exploration. The results revealed that creativity and innovation are transversal axes in the management of MSMEs and have allowed generating positive business results, which is confirmed by 92% of entrepreneurs. It is therefore concluded that creativity and innovation are elements that companies use in the development of business management.